IDENTIFIKASI BAHAYA, PENILAIAN DAN PENGENDALIAN RISIKO PADA PROSES PELEBURAN BAJA DI CV. SUMBER WAHYU DENGAN METODE HIRADC - Sutopo, Jaiz Wahyu; Ratriwhardani, Ratna Ayu (Universitas Of Surakarta, 2022)
Work Accidents are accidents that occur related to work, including diseases that arise due to work relations, as well as accidents that occur on the way to and from work. Work accidents can occur with risks ranging from low, medium, or high, one of which is when steel smelting which is an activity to melt steel so that an iron rod (billet) is produced which is then formed into various materials needed. Work safety can certainly be measured using a method called HIRADC. This method is able to provide identification of hazards, assessments and risks that may occur in steel smelting using a scale based on the resulting potential. This study aims to identify hazards and assess the risk of accidents in the steel smelting process at CV Sumber Wahyu using the HIRADC method. The result is that there are 36 risks with low, medium and high risk variations. The level of safety control on CV Sumber Wahyu is still very low, so various additional safety tools are needed must be owned.